Photocatalytic systems: reactions, mechanism, and applications - Mohamadpour, Farzaneh; Amani, Ali Mohammad (RSC advances, 2024)
The photocatalytic field revolves around the utilization of photon energy to initiate various chemical reactions using non-adsorbing substrates, through processes such as single electron transfer, energy transfer, or atom transfer. The efficiency of this field depends on the capacity of a light-absorbing metal complex, organic molecule, or substance (commonly referred to as photocatalysts or PCs) to execute these processes. Photoredox techniques utilize photocatalysts, which possess the essential characteristic of functioning as both an oxidizing and a reducing agent upon activation. In addition, it is commonly observed that photocatalysts exhibit optimal performance when irradiated with low-energy light sources, while still retaining their catalytic activity under ambient temperatures. The implementation of photoredox catalysis has resuscitated an array of synthesis realms, including but not limited to radical chemistry and photochemistry, ultimately affording prospects for the development of the reactions. Also, photoredox catalysis is utilized to resolve numerous challenges encountered in medicinal chemistry, as well as natural product synthesis. Moreover, its applications extend across diverse domains encompassing organic chemistry and catalysis. The significance of photoredox catalysts is rooted in their utilization across various fields, including biomedicine, environmental pollution management, and water purification. Of course, recently, research has evaluated photocatalysts in terms of cost, recyclability, and pollution of some photocatalysts and dyes from an environmental point of view. According to these new studies, there is a need for critical studies and reviews on photocatalysts and photocatalytic processes to provide a solution to reduce these limitations. As a future perspective for research on photocatalysts, it is necessary to put the goals of researchers on studies to overcome the limitations of the application and efficiency of photocatalysts to promote their use on a large scale for the development of industrial activities. Given the significant implications of the subject matter, this review seeks to delve into the fundamental tenets of the photocatalyst domain and its associated practical use cases. This review endeavors to demonstrate the prospective of a powerful tool known as photochemical catalysis and elucidate its underlying tenets. Additionally, another goal of this review is to expound upon the various applications of photocatalysts. The photocatalytic field revolves around the utilization of photon energy to initiate various chemical reactions using non-adsorbing substrates, through processes such as single electron transfer, energy transfer, or atom transfer.